Hubungan Pengetahuan dan Sikap Ibu Mengenai Stunting dengan Kejadian Stunting di Desa Pudun Jae, Kecamatan Padangsidempuan Batunadua, Kota Padangsidempuan, Sumatera Utara - Linda Mutiara Harahap; Fauziah Nasution; Elza Fauziah Harahap; Peby Utami; Wahyuni Juliani (Universitas Batanghari Jambi, 2023)
Stunting or short is a chronic malnutrition problem caused by a lack of nutritional intake for a long time, resulting in growth disorders in children, namely the child's height is lower or shorter (dwarf) than their age standard. This study aims to determine the frequency distribution of maternal knowledge and attitudes about stunting in toddlers in Padangsidempuan Batunadua district, Padangsidempuan city. This research uses quantitative methods with data collection techniques carried out through questionnaires, observations, and documentation. Data analysis using univariate analysis with assistance of the SPSS (Statistical Product and Service Solution) program. The sample was taken from 75 people using purposive sampling techniques which from toddler mothers. The results of the study proved that there was a relationship between maternal knowledge and attitudes towards stunting occurence in Pudun Jae village, Padangsidimpuan Batunadua district, Padangsidempuan city, North Sumatra.